Manganese accumulation and plant physiology behavior of Camellia oleifera in response to different levels of potassium fertilization. Issue 10 (23rd August 2020) - Yu, Fangming; Wang, Xueru; Yao, Yawei; Lin, Jiamin; Huang, Yuanyuan; Xie, Dongyu; Liu, Kehui; Li, Yi
Abstract: The effects of potassium (K) fertilization (KCl, analytically pure; 0, 60, 200, and 400 mg kg −1 ) on the growth and Mn accumulation of Camellia oleifera in two types of Mn-contaminated soils were investigated. The potential mechanisms underlying the impacts of K fertilization were explored. C. oleifera accumulated high amounts of Mn in both soil conditions. The addition of K fertilizer decreased the soil pH and promoted Mn accumulation in C. oleifera . However, the plant biomass decreased significantly under the high level of K fertilization (400 mg kg −1 ), and the oxidative stress was stimulated under Mn contamination. But an appropriate concentration of K fertilizer (200 mg kg −1 ) was necessary for the formation of photosynthesis pigments, nonenzymatic antioxidants and antioxidant enzymes, metabolic processes, and nutrient uptake. Furthermore, when plants supplemented with a low level of K fertilization (200 mg kg −1 ), the catalase activity in C. oleifera leaves was enhanced to alleviate oxidative stress and protect the plant from Mn contamination. Our study demonstrated that 200 mg kg −1 of K fertilizer has the potential to further enhance the efficiency of Mn phytoremediation by C. oleifera .